A highly energy-efficient magnetoelectric–photocatalytic coupling for water remediation. (April 2023) - PourhosseiniAsl, M.Javad; Berbille, A.; Tian, J.; Du, F.; Yu, Z.; Li, Z.; Guo, S.; Ren, K.; Dong, S.
Abstract: Contaminated water is one of the main infection routes for serious diseases, and water remediation of different environmental contaminations is an urge today. Here, we introduce a novel high-μ ribbon FeBSi–ZnO magnetoelectric (ME) nanocomposite that exhibits a magnetoelectric–photocatalytic (MEPC) coupling effect, which further enhances electrochemical activity for water remediation. Compared to the previously reported ultrasonic piezoelectric-photocatalytic technique, the proposed MEPC coupling system is 100–1200 times more energy-efficient. This energy-efficient catalysis can be attributed to the effective charge energy shifting generated by the low-power MEPC coupling system, which promotes the surface redox reaction via transferred electrons and holes and generation of the reactive oxygen species of O − 2 and OH . It is also found that the kinetic rate of organic pollutant degradation under MEPC activity is approximately three times faster than that of a pure PC process. The degradation efficiency for indigo carmine (IC), methyl orange (MO), and rhodamine B (RB) organic pollutants is 98% (less than 60 min), 97%, and 92% within 120 min, respectively. Also, MEPC activity could conduct 99.9% reduction of E. coli bacteria within 30 min. This study, therefore, provides an original MEPC system and an effective strategy for the sustainable environmental remediation endowed with an energy-efficient and low-cost nature owing to the multiphysical field synergetic effect. Highlights: A high-μ ribbon type FeBSi–ZnO magnetoelectric (ME) nanocomposite with a strong ME effect under a weak AC magnetic field. Magnetoelectric–photocatalytic (MEPC) coupling effect for water remediation. Energy-efficient MEPC system enhances the photocatalytic effect and generation of the reactive oxygen species.